Family Physician Perspectives on Primary Immunodeficiency Diseases - Orange, Jordan S.; Seeborg, Filiz O.; Boyle, Marcia; Scalchunes, Christopher; Hernandez-Trujillo, Vivian (Frontiers in Medicine, 2016)
Primary immunodeficiency diseases (PID) include over 250 diverse disorders. The current study assessed management of PID by family practice physicians. The American Academy of Allergy, Asthma, and Immunology Primary Immunodeficiency Committee and the Immune Deficiency Foundation conducted an incentivized mail survey of family practice physician members of the American Medical Association and the American Osteopathic Association in direct patient care. Responses were compared with subspecialist immunologist responses from a similar survey. Surveys were returned by 528 (of 4500 surveys mailed) family practice physicians, of whom 44% reported following ≥1 patient with a PID. Selective immunoglobulin A (IgA), deficiency (21%), and chronic granulomatous disease (11%) were most common and were followed by significantly more subspecialist immunologists (P<.0001). Use of intravenously administered Ig, and live viral vaccinations across PID was significantly different (P<.0001). Few family practice physicians were aware of professional guidelines for diagnosis and management of PID (4% vs. 79% of subspecialist immunologists, P<.0001). Family practice physicians will likely encounter patients with a PID diagnoses during their career. Differences in how family practice physicians and subspecialist immunologists manage patients with PID underscore areas where improved educational and training initiatives may benefit patient care.